2012
DOI: 10.1100/2012/849183
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Oxidative Effect of Long-Term Repetitive Hyperbaric Oxygen Exposures on Different Brain Regions of Rats

Abstract: Hyperbaric oxygen (HBO2) exposure affects both oxidative and antioxidant systems. This effect is positively correlated with the exposure time and duration of the treatment. The present study aims enlightening the relation of HBO2with oxidative/antioxidant systems when administered in a prolonged and repetitive manner in brain tissues of rats. Sixty rats were divided into 6 study (n Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
1
12
0
2
Order By: Relevance
“…Speit and Bonzheim [2003] implicated heme oxygenase-1 in HBO 2 -induced protection of A549 cells against oxygen toxicity induced by a second HBO 2 treatment 24 h later. Recently it was reported that daily exposure to 90 min HBO 2 @ 2.8 ATA for as many as 40 days failed to significantly elevated levels of MDA, protein carbonyl and glutathionine peroxidase in the cerebral cortex, inner white matter and cerebellum [Simsek et al, 2012]. These findings, albeit at a lower atmospheric pressure than that applied in the present study, as well as our results are consistent in demonstrating a lack of oxygen toxicity.…”
Section: Discussionsupporting
confidence: 93%
“…Speit and Bonzheim [2003] implicated heme oxygenase-1 in HBO 2 -induced protection of A549 cells against oxygen toxicity induced by a second HBO 2 treatment 24 h later. Recently it was reported that daily exposure to 90 min HBO 2 @ 2.8 ATA for as many as 40 days failed to significantly elevated levels of MDA, protein carbonyl and glutathionine peroxidase in the cerebral cortex, inner white matter and cerebellum [Simsek et al, 2012]. These findings, albeit at a lower atmospheric pressure than that applied in the present study, as well as our results are consistent in demonstrating a lack of oxygen toxicity.…”
Section: Discussionsupporting
confidence: 93%
“…Another experimental set revealed an important finding that the enhanced levels of oxidation products declined to their baseline values at one hour later following a single HBO exposure (13,14). Finally, in our most recent studies, different from the abovementioned one-session HBO exposure procedures, after exposure to daily HBO sessions for up to 8 weeks, clear rises in lipid and protein oxidation products along with the antioxidant enzyme superoxide dismutase (SOD) were detected in the rats' lung (15), but not in their brain tissue (16).…”
Section: Introductionmentioning
confidence: 60%
“…The good news was that increased activities of antioxidant enzymes accompanied the rise of these oxidation products. On the other hand, the brain tissue specimens of rats did not reflect any significant change for oxidant and antioxidant indices in the same experimental set (16). With regard to hyperoxia-induced oxidative injury, the lung tissue is the first target, since it is the entering site of oxygen; then, oxygen passes into the blood and the oxygen-carrier cells, erythrocytes, represent an ideal secondary target for detecting hyperoxic oxidative interactions (9).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Nevertheless, ROS have also been suggested to mediate useful actions in relation to cellular functions [6][7][8]. Although there are some experimental studies showing that HBO promotes antioxidant activity by providing more oxygen to the body and thus decreasing the production of ROS and lipid peroxidation, these results have not been validated [9]. Inflammatory response is a broad pathophysiological process.…”
Section: Introductionmentioning
confidence: 99%